BILATERAL OVARIAN CARCINOSARCOMA (CASE REPORT) - E. A. Fesik; L. N. Bondar; V. M. Perelmuter; S. V. Molchanov; L. A. Kolomiec (Сибирский онкологический журнал, 2016)
A rare clinical case of bilateral carcinosarcoma of the ovary including a rare combination of serous adenocarcinoma and endometrial stromal sarcoma has been presented.